Studies on the feasibility of a pneumatic injector for seeding of rice - LIYA JOY SREEJA S SUSHIL SIVARAM; Er. Manoj Mathew (Guide) (Tavanur 2005 Kelappaji College of Agricultural Engineering and Technology)
to design and develop a pneumatic paddy seed injector. to test the performance of paddy seed injector. three models.
Studies on the feasibility of a pneumatic injector for seeding of rice